Taurine stimulates proliferation of mice embryonic cultured neural progenitor cells - Hernández-Benítez, Reyna; Pasantes-Morales, Herminia; Saldaña, Ismael Torres; Ramos-Mandujano, Gerardo (Journal of neuroscience research, 2010)
Taurine is present in high levels in fetal brain which decrease in the adult, suggesting its role in brain development. In some regions of taurine deficient animals cells show defective migration and the presence of numerous mitotic figures, suggesting a delay in cell proliferation. To know more about the role of taurine in the developing brain cells, the present study investigated whether taurine is a factor involved in proliferation or/and viability of neural progenitor cells (NPC). NPC were obtained from 13.5‐days mice embryos mesencephalon, and cultured during 4–5 days to form neurospheres in the presence of EGF plus FGFb (EGF/FGF) or EGF alone. Mesencephalon taurine content (349 mmoles/kg protein) was lost in NPC and recovered after addition of 10 mM taurine to the culture. Neurospheres‐forming NPC were over 94% nestin‐positive. Taurine increased 38.6% and 43.2% the number of NPC formed in EGF/FGF or EGF conditions, respectively. In secondary neurospheres this increase was 24.6% and 62.1%, in EGF/FGF or EGF cultures respectively. Correspondingly neurospheres size was increased by taurine but neurospheres number was not enhanced. Taurine significantly increased the number of BrdU‐positive cells, without affecting cell viability, suggesting proliferation as the mechanism responsible for taurine action increasing NPC. Taurine seems unable to increase the number of β‐III‐tubulin‐positive cells differentiated from neurospheres after serum addition, and rather an increase in astrocytes was observed. These results point to taurine as a trophic factor contributing to optimize NPC proliferation. © 2009 Wiley‐Liss, Inc.